Culturally Adapting a Video-Based Self-acupressure Intervention to Manage Symptoms for Black and Latina Breast Cancer Survivors - Katarina E. AuBuchon; Amrita Bonthu; Lourdes Inbar-Albo; Thelma D. Jones; Jacqueline Beale; Claudia Campos-Galván; Laura A. Logie; Carla Arieta; Geng-Hao Liu; Alejandra Hurtado-de-Mendoza; Suzanne C. Danhauer; Kristi D. Graves; et al. (Journal of Cancer Education, 2026)
Black and Latina breast cancer survivors (BCS) experience greater physical functioning decline and symptom burden than non-Hispanic White BCS, partially due to systemic racism and socioeconomic barriers. Self-administered acupressure has shown promising effects for reducing cancer-related symptoms and is a low-cost, integrative approach to managing symptoms. However, self-acupressure has not been tested in Black and Latina BCS. This study aimed to culturally adapt an existing self-acupressure video intervention and assess Black and Latina BCS’s feedback on the acceptability of the adapted video. Following learner verification and revision methods, we collaborated with community organizations and partners for cultural and linguistic adaptation of the existing video. We conducted semi-structured interviews with four community partners, two oncology providers, and six Black and Latina BCS to gather feedback on content comprehension, engagement, cultural acceptability, and satisfaction with the intervention. We made iterative revisions to the video and then conducted usability testing with the six BCS. We produced an 11-min self-acupressure video following participant feedback, including a need for clear differentiation between acupressure and acupuncture, simplified explanations of physiological effects of self-acupressure, increased culturally relevant presentation by including Black and Latina BCS performing acupressure demonstrations, testimonial segments, and lay language explanations. In usability testing, the six BCS rated the intervention highly. Black and Latina BCS were highly satisfied with the culturally adapted self-acupressure video and expressed strong interest in performing self-acupressure. Future studies will evaluate the intervention’s effects on symptom management and quality of life in these underrepresented populations.

Correction: Culturally Adapting a Video-Based Self-acupressure Intervention to Manage Symptoms for Black and Latina Breast Cancer Survivors - Katarina E. AuBuchon; Amrita Bonthu; Lourdes Inbar-Albo; Thelma D. Jones; Jacqueline Beale; Claudia Campos-Galván; Laura A. Logie; Carla Arieta; Geng-Hao Liu; Alejandra Hurtado-de-Mendoza; Suzanne C. Danhauer; Kristi D. Graves; et al. (Journal of Cancer Education, 2025)

The Response and Recovery of Carbon and Water Fluxes in Australian Ecosystems Exposed to Severe Drought - C. Stephens; B. Medlyn; L. Williams; J. Knauer; A. Inbar; E. Pendall; S. K. Arndt; J. Beringer; C. M. Ewenz; N. Hinko‐Najera; L. B. Hutley; P. Isaac; et al. (Global Change Biology, 2025)
Climate change‐driven increases in drought risk pose a critical threat to global carbon and water cycles. However, ecosystem‐scale responses remain poorly quantified, particularly for severe, multiyear drought events. We addressed this gap by examining ecosystem‐scale carbon and water flux sensitivity to the extreme 2018–19 drought in Australia using data from 14 eddy covariance flux sites. The ecosystems span grasslands and semi‐arid woodlands to tropical and temperate forests. The driest sites (classed as “grass” and “very dry”) experienced drastic productivity impacts, with a 65% decrease in Gross Primary Productivity (GPP) over 2 years relative to the pre‐drought average. However, fluxes in “dry,” “seasonally wet” and “wet” ecosystems showed remarkable resistance, with no overall change in GPP. All sites recovered rapidly; carbon fluxes in the first post‐drought year matched (and generally exceeded) those of a climatically similar pre‐drought year. Drought responses were strongly mediated by ecosystem‐specific strategies. The driest ecosystems showed direct coupling of productivity to water availability, while intermediate ecosystems (dry and seasonally wet) leveraged stored soil water to maintain evapotranspiration and productivity under drought. At these sites, water was conserved over wet periods (evapotranspiration rainfall). This mechanism mitigating periodic water stress under high rainfall variability likely contributed to the notable drought resistance of the dry and seasonally wet sites. The monthly water deficit index (MWDI) emerged as a robust predictor of productivity across space, highlighting that short‐term water availability deficits strongly influence overall ecosystem composition. Analysis of drought response mechanisms suggested rapid leaf loss under water stress, particularly at the driest sites. Our findings underscore the importance of accounting for sub‐surface water storage and diverse drought response strategies in vegetation models. We provide critical benchmarks for improving parameterization of plant‐water relations, aiding efforts to inform climate‐robust management strategies.

Introducing dynamics into coastal recreational management: Humans-sharks interactions case study - Shiri Zemah-Shamir; Inbar Schwartz Belkin; Ziv Zemah-Shamir; Michelle E. Portman (Ocean & Coastal Management, 2025)

Exploring barriers to the implementation of geospatial technologies in marine spatial planning: Reports from practitioners - Inbar Schwartz-Belkin; Michelle E. Portman (Marine Policy, 2024)

Comparing spatial management tools to protect highly migratory shark species in the Eastern Mediterranean Sea hot spots - Shiri Zemah-Shamir; Ziv Zemah-Shamir; Yoav Peled; Ole Johannes Ringnander Sørensen; Inbar Schwartz Belkin; Michelle E. Portman (Journal of Environmental Management, 2023)

A review of geospatial technologies for improving Marine Spatial Planning: Challenges and opportunities - Inbar Schwartz-Belkin; Michelle E. Portman (Ocean & Coastal Management, 2023)

Development of the Inland Sea and its evaporites in the Jordan-Dead Sea Transform based on hydrogeochemical considerations and the geological consequences - Peter Möller; E. Rosenthal; N. Inbar; C. Siebert (International Journal of Earth Sciences, 2018)

Plant cell piercing by a predatory mite: evidence and implications - E. Adar; M. Inbar; S. Gal; L. Issman; E. Palevsky (Experimental and Applied Acarology, 2015)

On the effects of adaptation to changing loads on movement-related EEG potentials - I. Makienko; E. Yom Tov; G. F. Inbar (Biological Cybernetics, 2005)

Detection of movement-related potentials from the electro-encephalogram for possible use in a brain-computer interface - E. Yom-Tov; G. F. Inbar (Medical & Biological Engineering & Computing, 2003)

Movement-related potentials during the performance of a motor task I: The effect of learning and force - E. Yom-Tov; A. Grossman; G. F. Inbar (Biological Cybernetics, 2001)

Movement-related potentials during the performance of a motor task II: Cerebral areas activated during learning of the task - E. Yom-Tov; A. Grossman; G. F. Inbar (Biological Cybernetics, 2001)

Abstracts of Presentations at the 18th Conference of the Entomological Society of Israel - M. P. Pener; L. Anshelevich; E. Dunkelblum; M. Hard; A. Harari; D. Gordon; M. Kehat; H. Reuveny; O. Akunis; D. Oppenheim; E. Dunkelblum; Acta Rafaeli; et al. (Phytoparasitica, 2001)

Unilateral Vocal Cord Paralysis as a Result of a Nocardia farcinica Laryngeal Abscess - E. Cohen; D. Blickstein; E. Inbar; Z. Samra; M. Weinberger (European Journal of Clinical Microbiology & Infectious Diseases, 2000)